Impact of Non-vitamin K Antagonist Oral Anticoagulant Withdrawal on Stroke Outcomes - Park, Joong Hyun; Han, Sang Won; Lee, Kyung-Yul; Choi, Hye-Yeon; Cheon, Kyeongyeol; Cho, Han-Jin; Jung, Yo Han; Park, Hyung Jong; Nam, Hyo Suk; Heo, Ji Hoe; Lee, Hye Sun; Saposnik, Gustavo; et al. (Frontiers in Neurology, 2018)
Introduction: Discontinuation of oral anticoagulants such as non-vitamin K antagonist oral anticoagulants (NOACs) may induce a hypercoagulable state, leading to severe stroke and poor outcomes. This study aimed to compare stroke outcomes between NOACs withdrawal and other prior medication statuses in patients with non-valvular atrial fibrillation (NVAF). Methods: Consecutive patients who had pre-existing NVAF and were admitted for an acute ischemic stroke or transient ischemic attack- at five hospitals between January 2013 and December 2016 were included. Prior medication status was categorized into seven groups such as no antithrombotics, antiplatelet-only, warfarin with subtherapeutic intensity, warfarin with therapeutic intensity, NOAC, warfarin withdrawal, and NOAC withdrawal. We compared initial National Institute of Health Stroke Scale (NIHSS) scores between groups Results: Among 719 patients with NVAF, The median NIHSS score at admission was 5 (IQR 1-13). The NOAC withdrawal group had the highest median NIHSS scores at stroke onset [16, interquartile range, IQR (1–17)], followed by the warfarin withdrawal group [11, IQR (1–14, 18)], the no antithrombotic group [5, IQR (1–13, 18, 19)], and the warfarin with subtherapeutic intensity group [5, IQR (1–10, 18, 19)]. A Multivariable analysis demonstrated that NOAC withdrawal was independently associated with higher NIHSS scores at stroke onset (B 4.645, 95% confidence interval 0.384–8.906, P = 0.033). The median interval from drug withdrawal to ischemic stroke or TIA was 7 days (IQR 4-15) in the NOAC group. Conclusions: Stroke that occurred after stopping oral anticoagulants, especially NOAC, and was more severe at presentation and associated with poorer outcomes.